A variable kinematic one-dimensional model for the hygro-mechanical analysis of composite materials. (15th June 2020) - Severino, S.; Zappino, E.; Pagani, A.; Gigliotti, M.; Pannier, Y.; Carrera, E.
Abstract: An advanced modeling technique for hygro-mechanical analyses has been discussed in the present work. A three-dimensional closed-form solution of the diffusion equation has been developed and used to evaluate the time evolution of the moisture concentration in a composite coupon. A refined kinematic one-dimensional model, derived in the framework of the Carrera unified formulation, has been extended to the hygro-mechanical analysis of composites. The present one-dimensional model has been used to predict the stress evolution in a composite specimen using the moisture concentration, deriving from the analytical solution, as boundary conditions. The results have been compared with those from a solid model derived in by means of the commercial tool Abaqus. The performances of the present approach have been investigated through a convergence analysis. The results demonstrate the numerical efficiency of the present one-dimensional model that can provide a three-dimensional solution with a reduction in the computational cost with respect to the classical solid model.